(untitled) (Communications in Computational Physics, 2018)
In this paper, a multilevel domain decomposition approach based on multigrid methods for obtaining fast solutions for coupled engineering flow applications arising on complex domains is presented. The proposed technique not only allows solutions to be computed efficiently at the element level but also helps us to achieve proper accuracy, load balancing and computational efficiency. Numerical results presented demonstrate the robustness of the proposed technique.